A Quality Improvement Initiative to Standardize Use of Inhaled Nitric Oxide in the PICU. Issue 2 (March 2017) - Karsies, Todd J.; Evans, Laura; Frost, Randall; Ayad, Onsy; McClead, Richard
Abstract : Background: Inhaled nitric oxide (iNO) is a potent pulmonary vasodilator used off-label to treat refractory hypoxemia in the pediatric intensive care unit (PICU). However, clinical practice varies widely, and there is limited evidence to support this expensive therapy. Our objective was to test whether implementation of a clinical guideline for iNO therapy would decrease practice variability, reduce ineffective iNO utilization, and control iNO-related costs. Methods: We used quality improvement (QI) methodology to standardize the use of iNO in a single quaternary care PICU (noncardiac). All PICU patients receiving iNO therapy between January 1, 2010, and December 31, 2013, were included. The QI intervention was the development and implementation of a clinical guideline for iNO initiation, continuation, and weaning. iNO use was monitored using statistical process control charts. Results: We derived baseline data from 30 preguideline patients (35 separate iNO courses) compared with 33 postguideline patients (36 separate iNO courses). Despite similar baseline characteristics, disease severity, and degree of hypoxemia, postguideline patients had a shorter median [interquartile range (IQR)] duration of iNO therapy than preguideline patients [76 (48–124) hours versus 162 (87–290) hours; P < 0.0001]. We have sustained the reduced iNO usage throughout the postguideline period. Postguideline patients also had improved provider documentation and a median iNO cost savings of $4, 600. Conclusions: Implementation of iNO usage guidelines was associated with decreased iNO usage and cost of iNO therapy in the PICU.